Il turismo come regime an-estetico - De Pascale, Imma (Scenari, 2025)
The article proposes a reflection on mass tourism in relation to “art cities” taken by storm by millions of visitors intent on capturing on camera their presence in places conventionally recognized as having cultural value. In particular, the object of investigation is the mechanisms inflicted by capitalist culture that deceives the tourist into an aesthetic experience free from the constraints of everyday life. The purpose is to highlight the dark side of the tourism industry: tourism, as we know it today, is a vehicle of social control, an institutional vent that the capitalist system grants citizens as a reward to better endure oppression.